MINIMUM DOMINATING DISTANCE ENERGY OF A GRAPH - kanna, rajesh; B N, DHARMENDRA; G, SRIDHARA (IndoMS, 2014)
Recently we introduced the concept of minimum dominating energy[21]. Motivatedby this paper,we introduced the concept of minimum dominating distance energyEDd(G) of a graph G and computed minimum dominating distance energies of a Stargraph,Complete graph,Crown graph and Cocktail graphs. Upper and lower boundsfor EDd(G) are also established.DOI :Â http://dx.doi.org/10.22342/jims.20.1.133.19-29